2020
DOI: 10.1016/j.seizure.2020.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the seizure-free outcome and visual field deficits between anterior temporal lobectomy and selective amygdalohippocampectomy: A systematic review and meta-analysis

Abstract: The purpose of our study is to compare seizure-free outcome and the incidence of visual field deficits (VFD) between anterior temporal lobectomy (ATL) and selective amygdalohippocampectomy (SAH) among patients with intractable temporal lobe epilepsy (TLE). Methods: We searched MEDLINE, Embase and Cochrane databases using keywords related to ATL, SAH and VFD. Previous studies that compared ATL and SAH with seizure-free outcome and the incidence of VFD were included. A fixed-effect model was used to conduct meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For this reason, the search strategy for ATL and sAHE was adapted so that only randomized controlled trials (RCTs) and (retrospective/prospective) comparative studies between ATL and sAHE were included. The comparative studies were extracted from two recent high‐quality comprehensive systematic reviews 15,16 . Among the various classifications established for the outcome after epilepsy surgery or intervention, the Engel Epilepsy Surgery Outcome Scale was used most frequently among the studies examined so that only studies that included this classification were selected for the final analysis 17…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the search strategy for ATL and sAHE was adapted so that only randomized controlled trials (RCTs) and (retrospective/prospective) comparative studies between ATL and sAHE were included. The comparative studies were extracted from two recent high‐quality comprehensive systematic reviews 15,16 . Among the various classifications established for the outcome after epilepsy surgery or intervention, the Engel Epilepsy Surgery Outcome Scale was used most frequently among the studies examined so that only studies that included this classification were selected for the final analysis 17…”
Section: Methodsmentioning
confidence: 99%
“…The comparative studies were extracted from two recent high-quality comprehensive systematic reviews. 15,16 Among the various classifications established for the outcome after epilepsy surgery or intervention, the Engel Epilepsy Surgery Outcome Scale was used most frequently among the studies examined so that only studies that included this classification were selected for the final analysis. 17 Eligible studies were required to meet the following criteria: In cases where a study was a follow-up to or an expansion of an already published cohort, the paper reporting on the more detailed and comprehensive dataset was included.…”
Section: Key Pointsmentioning
confidence: 99%
“…Furthermore, there is a lack of consensus concerning the visual outcomes of SAHE and ATL. Although Xu et al showed a lower incidence of VFDs following SAHE, 14 their recommendation is based on a small number of studies. Especially single‐center studies directly comparing surgical techniques are scarce.…”
Section: Introductionmentioning
confidence: 98%
“…This improves to 73% when surgical intervention is undertaken within 2 years of the onset of disabling seizures 2 . As the benefit of surgical resections for drug-refractory mesial temporal lobe epilepsy became more apparent an increasing number of patients became seizure-free but were not eligible for a driving licence due to the magnitude of the resulting VFD 3 . In many countries, VFDs along the horizontal meridian within an area subtending 120 degrees or a significant defect within the central +/-20 degrees during binocular Esterman protocol assessment would preclude eligibility for a driving licence.…”
Section: Introductionmentioning
confidence: 99%